Trajectory schooling of youth and adults in Brazil: of government platforms to the pedagogical proposals emptied - Friedrich, Marcia (2010)
This article provides a historical approach of Schooling for Youth and Adults and its trajectory in the history of education in Brazil. It is characterized by an analysis documentary on the movement of this type of education and public policies that govern it. We compare with the historical development, teacher training, the labor market in Brazil, using primary and secondary sources with the search including the period from 1973 to 2007. We note that literature in general, describes events chronologically ad hoc initiatives in an attempt to solve the problems of illiteracy and lack of qualification of the workforce necessary for the current method of production each season, as initiatives for public policies. Regarding the relationship with the educational proposals for this type of education based on the analysis of legal documents, guidelines and programs for the Brazilian educational context, they are characterized by a compensatory, supplementary, and emergency education.